Attitudes of Female Master’s students in Instructional Technology Program at Najran University towards the Use of Augmented Reality Technology - Alyami, Shroug Mesali Saleh (Journal of Educational and Psychological Sciences, 2023)
This research aims at determining the Attitudes of Female Master’s students in Instructional Technology Program at Najran University towards the Use of Augmented Reality Technology. The researcher used descriptive approach and questionnaire and forming one point included Attitudes of Female Master’s students in Instructional Technology Program at Najran University towards the Use of Augmented Reality Technology.Where the study was applied on (92) Students of Master Degree of Najran University in major Education Technologies for the year 1443H ,1st semester.The research concluded that all female students have positive attitudes towards using of Augmented Reality. Also it pointed that no Statistical indication variations in the attitudes of Master Degree Students towards using of Augmented Reality related to variations of ( profession , training courses and previous major) where in recommended the importance of Augmented Reality technology application in education that for resolving education problems , increasing training courses for students.